(untitled) (Ustozlar uchun, 2025)
This paper examines the role and importance of creative tasks in the development of children’s cognitive, emotional, and social skills. Creative activities—such as storytelling, drawing, role-playing, problem-solving, and project-based learning—help children express themselves freely, think independently, and develop imagination and critical thinking. The study highlights how creativity supports language development, motivation, and self-confidence in educational settings. Furthermore, it discusses the teacher’s role in designing and implementing creative tasks that cater to individual learning styles. The paper concludes that integrating creative activities into daily lessons enhances not only academic achievement but also emotional intelligence and lifelong learning abilities.